Better efficacy of sequential combination with balloon pulmonary angioplasty after long‐term riociguat for patients with inoperable chronic thromboembolic pulmonary hypertension - Wei Wang; Jianfeng Wang; Suqiao Yang; Tuguang Kuang; Yidan Li; Juanni Gong; Yuanhua Yang (Pulmonary Circulation, 2024)
Abstract The present study aimed to evaluate the efficacy of long‐term riociguat sequentially combined with balloon pulmonary angioplasty (BPA) for patients with inoperable chronic thromboembolic pulmonary hypertension (CTEPH). Eight inoperable CTEPH patients were enrolled in this study, who have been administrated riociguat 2.5 mg three times daily for about 8 years, then underwent several sessions of BPA procedures. Data are prospectively collected to evaluate clinical outcomes, hemodynamics, exercise capacity, and right heart size and function by echocardiography at baseline, 8 years after riociguat, and 3 months after the final BPA. Eight patients (mean age 54.9 ± 11.4 years) were treated with riociguat 2.5 mg three times daily for 95.0 ± 10.7 months. Cardiac index (CI) (1.5 ± 0.5 L/min/m2 to 2.4 ± 0.6 L/min/m2, p = 0.005), 6 min walking distance (6MWD) (329.6 ± 87.5 m to 418.1 ± 75.8 m, p = 0.016), and pulmonary vascular resistance (PVR) (1336.9 ± 320.2 dyn·s·cm−5 to 815.4 ± 195.6 dyn·s·cm−5, p = 0.008) were significant improvement after riociguat treatment. Mean 4.1 ± 1.6 additional combinational BPA sessions and mean 18.8 ± 8.1 balloon dilations were performed. Mean pulmonary artery pressure (54.1 ± 11.1 mmHg to 33.6 ± 7.7 mmHg, p = 0.002) and PVR (815.4 ± 195.6 dyn·s·cm−5 to 428.3 ± 151.2 dyn·s·cm−5, p＜0.001) were further decreased. CI (2.4 ± 0.6 L/min/m2 to 2.7 ± 0.7 L/min/m2, p = 0.028) and 6MWD (418.1 ± 75.8 m to 455.7 ± 100.0 m, p = 0.038) were increased significantly. After long‐term riociguat treatment, sequential combination with BPA delivered considerably incremental benefits on exercise capacity and pulmonary hemodynamics, as well as right heart size and function of technically inoperable CTEPH patients.